Methylases and methylation in gene regulation in Pseudomonas syringae - Mancera-Miranda, Laura; López-Pagán, Nieves; Ruiz-Albert, Francisco Javier; Beuzón-López, Carmen del Rosario (My University, 2022)
DNA methylation carried out by methyltransferases not associated with restriction enzymes, known as orphan methyltransferases, is an epigenetic mechanism widely spread in bacteria and archea. These orphan methylases show motif specificities and methylation patterns that support their function in gene regulation and DNA replication [1]. In E. coli and Salmonella, this mechanism has been related to the regulation of the initiation of replication, DNA mismatch repair and transcription. DNA methylation is also involved in generating phenotypic heterogeneity within clonal populations in these species, with strong implications for virulence [2]. However, little is known about the role of methylation in Pseudomonas syringae. P. syringae is a relevant phytopathogenic bacteria, responsible for a great variety of plant diseases and with a huge impact in crop production worlwide. This bacteria is also used as a model for the study of plant-pathogen interactions [3]. In order to unveil the importance of methylation in P. syringae, we decided to address the characterization of this epigenetic process in this pathogenic bacteria. For that, we have studied the methylases identified in P. syringae, and established its methylome. Regarding the methylome, we have identified several methylation motifs.
Keywords: Pseudomonas syringae; Pseudomonas syringae